The executive statutes of Companies Law No. 159/1981 as amended up to Feb. 1999 / Translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Part one:on foundation of companies. - chapter one:foundation of shareholder companies, joint stock companies with shares. - chapter two: establishing a company with limited liabilities. - chapter three:on measures of declaration and publication..5 -- part two:on provisions connected with forms of companies. - chapter one:shareholder companies and joint stock companies with shares. - chapter two:limited liability company. -- part three:merger and change of company legal form. - chapter one:merger. - chapter two:changing the company legal form. -- part four: control and inspection. - chapter one:control and access rights. - chapter two:certain inspection measures. -- part five: branches and offices representing foreign firms. - chapter one: foreign firms branches. –chapter two: representation offices...etc. -- part six: transitional closing and provisions.